Гуманітарна дипломатія: історія становлення та сучасність - Окладна, Марина Георгіївна; Перевалова, Людмила Вікторівна; Генкул, Юлія Володимирівна (НДІ правового забезпечення інноваційного розвитку НАПрН України, 2021)
В статті досліджуються передумови та особливості формування гуманітарної дипломатії і гуманітарного права. Автори намагаються дати сучасне визначення поняття «гуманітарна дипломатія, здійснюють аналіз історичного розвитку концепції міжнародного гуманітарного права та дипломатії». Висвітлюється роль міжнародних організацій в здійсненні гуманітарної допомоги уразливим групам населення під час збройних конфліктів, охарактеризовані сучасні проблеми функціонування гуманітарної дипломатії.

Ensuring constant access to humanitarian aid during military conflicts and complex emergencies has always been an important issue for politicians. Its solution is to guarantee the protection of civilians in times of danger and political instability. The practice of humanitarian negotiations led to the emergence of the concept of humanitarian diplomacy in the early 2000s. It was to persuade community leaders and high-ranking decision-makers to act in the interests of vulnerable populations in accordance with humanitarian principles. Humanitarian diplomacy is carried out by humanitarian actors and includes the organization of a safe presence of humanitarian organizations, access to negotiations with the civilian population, monitoring assistance programs, and respect for international law. The development of humanitarian aspects of diplomacy is linked to the protection of the most vulnerable groups - ethnic and religious minorities, women, children, refugees, victims of armed conflict, terrorism and environmental disasters. An important task facing scholars is to study the nature of diplomacy, the history of its development, as well as modern models and tools. Scholars draw attention to the need to return in international relations to the philosophy of morality and values. In our opinion, it is expedient to define the concept of humanitarian diplomacy, to show the formation and development of humanitarian diplomacy and the institute of humanitarian law, to consider the problems of humanitarian activity in themodern world.
Keywords: гуманітарна дипломатія; гуманітарна допомога; права людини; дипломатичні відносини; кризи; міжнародне гуманітарне право; humanitarian diplomacy; humanitarian aid; human rights; diplomatic relations; crises; international humanitarian law